Many-body effect renders universal subdiffusion to water on different proteins - Song Li; Pan Tan; Jun Li; Min Tang; Liang Hong (Physical Review Research, 2022)
Diffusion of interfacial water is crucial for the function and stability of enclosed protein molecule. By combining neutron scattering and molecular dynamics simulation results, we found that the interfacial water on different proteins including intrinsically disordered proteins exhibit a universal subdiffusive motion with a common power law. Further analysis of the simulation trajectories and analytical modeling reveal that it is the many-body effect, i.e., water prefers to jump between shallow trapping sites on the protein as the deep ones are mostly occupied, that overrides the surface differences among proteins to render the interfacial water universal subdiffusion.